Perancangan Ulang Identitas Visual Yangko Pak Prapto Dengan Kemasan Sebagai Media Utama - Maxellino Putra Wijaya; Yana Erlyana (ULTIMART Jurnal Komunikasi Visual, 2022)
Yangko is Indonesian traditional food originating from Yogyakarta City. One of the famous yangko brands is Yangko Pak Prapto, it is an old brand established in 1970. Market competition makes a brand require the right branding strategy to be able to compete, has a strong identity to differentiate itself from other brands and is easy to remember by consumers. The problem is that the Yangko Pak Prapto brand can't compete because they lack branding strategy and promotion. Rebranding can be chosen to strengthen brand identity and attract new customers, one of the strategies by using packaging as the main media because packaging is part of the product that deals visually directly with customers. The method in this research uses descriptive qualitative research methods, and the design process uses the design thinking method. The focus of this research is to redesign the yangko pak prapto brand through packaging as main media, with the hope that the brand can have a strong visual identity and increase sales, and can also be a good example in developing a local MSME brand. The results of the design will be in the form of a new logo, new packaging and several supporting media. Keywords: rebranding; brand identity; packaging design; yangko pak prapto; msmes; local product.